MATHEMATICAL MODEL OF CHEMICAL PURIFICATION OF WATER IN A MECHANICAL FILTER - Chernukha, Olha; Bilushchak, Yurii; Chuchvara, Anastasiia (Collection of scientific papers «ΛΌГOΣ», 2022)
Based on the thermodynamic approach, a mathematical model of chemical water purification in a mechanical filter is constructed. For each of the components of the system, the mass transfer equation is obtained, on the basis of which the initial-boundary value problem of convective diffusion accompanied by a chemical reaction is formulated. Considering the terms corresponding to the components generated as a result of chemical reactions as internal sources, the system of integro-differential equations is assigned with the original initial-boundary value problem. The solution of this system is found by the method of successive iterations.